How balance task-specific training contributes to improving physical function in older subjects undergoing rehabilitation following hip fracture: a randomized controlled trial - Monticone, Marco; Ambrosini, Emilia; Brunati, Roberto; Capone, Antonio; Pagliari, Giulia; Secci, Claudio; Zatti, Giovanni; Ferrante, Simona (Clinical rehabilitation, 2018)
To evaluate the efficacy of a rehabilitation programme including balance task-specific training in improving physical function, pain, activities of daily living (ADL), balance and quality of life in subjects after a hip fracture. Randomized controlled trial. A total of 52 older subjects selected for internal fixation due to extra-capsular hip fracture were randomized to be included in an experimental ( n = 26) and control group ( n = 26). The experimental group underwent a rehabilitation programme based on balance task-specific training. The control group underwent general physiotherapy, including open kinetic chain exercises and walking training. Both groups individually followed programmes of 90-minute sessions five times/week for three weeks. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), a Pain Numerical Rating Scale, the Berg Balance Scale, the Functional Independence Measure and the 36-item Short-Form Health Survey. The participants were evaluated before and after training, and after 12 months. Significant effects of time, group and time × group were found for all outcome measures in favour of the experimental group. A clinically important between-group difference of 25 points was achieved after training and at follow-up in terms of the primary outcome (WOMAC function before treatment, after treatment and at follow-up was 84.8 (3.7), 39.8 (4.9) and 35.7 (6.2) for the experimental group and 80.9 (5.7), 65.2 (7.1) and 61.0 (11.1) for the control group). An inpatient rehabilitation programme based on balance task-specific training is useful in improving physical function, pain, ADL and quality of life in older patients after hip fracture.